Liquid crystal compound containing polyfluorophenanthrene structure and application thereof
By developing negative dielectric anisotropic liquid crystal compounds containing polyfluorophylline structures, the shortcomings of existing liquid crystal materials in low voltage driving, fast response and low temperature stability are solved, and efficient liquid crystal display performance is achieved.
Patent Information
- Application Number
- CN202310152116.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-22
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2043-02-22
AI Technical Summary
Existing liquid crystal materials have shortcomings in achieving low voltage driving, fast response, wide temperature range and good low temperature stability, especially in reducing rotational viscosity and improving dielectric anisotropy.
A negative dielectric anisotropic liquid crystal compound containing a polyfluorophylene structure is developed, which has high negative dielectric anisotropy, good liquid crystal mutual solubility and relatively low rotational viscosity through a specific molecular structure design.
The liquid crystal compound can effectively reduce the driving voltage and improve the response speed of the liquid crystal display device, while maintaining moderate optical anisotropy values and good charge retention rates, meeting the multiple requirements of the liquid crystal display for performance.
Smart Images

Figure CN116410756B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of liquid crystal compounds, in particular to a novel liquid crystal compound containing a polyfluorophenanthrene structure, and also to applications thereof. Background Art
[0002] In recent years, the development of liquid crystal display devices has been increasingly rapid, and different types of liquid crystal display devices have also appeared, such as small car-mounted liquid crystal display devices, portable liquid crystal display devices, ultra-thin liquid crystal display devices, etc. The development of the liquid crystal display field is making progress. Taking television as an example, its advantages are light weight, small space occupation, and more convenient movement. Convenient liquid crystal display devices such as notebook personal computers, handheld computers, and mobile phones have also appeared.
[0003] The application of liquid crystal materials as environmental materials in the fields of information display materials, organic optoelectronic materials, etc. has great research value and bright application prospects. At present, TFT-LCD product technology has matured, and it has successfully solved technical problems in viewing angle, resolution, color saturation and brightness. Large-size and small-size TFT-LCD displays have gradually occupied the mainstream position of flat-panel displays in their respective fields. However, the requirements for display technology have been constantly increasing, such as requiring liquid crystal displays to achieve faster response, reduce driving voltage to reduce power consumption, etc., which also requires liquid crystal materials to have low voltage drive, fast response, wide temperature range and good low-temperature stability.
[0004] Liquid crystal materials themselves play an important role in improving the performance of liquid crystal displays, especially reducing the rotational viscosity of liquid crystal materials and increasing the dielectric anisotropy △ε of liquid crystal materials, which will significantly improve the performance of liquid crystal displays. Therefore, in order to improve the performance of liquid crystal materials and adapt them to new requirements, the synthesis of new structural liquid crystal compounds and the study of structure-performance relationships have become an important task in the field of liquid crystals. Summary of the invention
[0005] The purpose of the present invention is to develop a new negative dielectric anisotropy liquid crystal compound containing a polyfluorophenanthrene structure, which has excellent properties such as high negative dielectric anisotropy, good liquid crystal mutual solubility, and relatively low rotational viscosity, and can be used to improve the performance of liquid crystal materials.
[0006] In a first aspect, the present invention provides a liquid crystal compound, which comprises a structure represented by general formula (I):
[0007]
[0008] in:
[0009] R1 and R2 each independently represent an alkyl group or alkoxy group having 1 to 12 carbon atoms, a cycloalkyl group having 3 to 8 carbon atoms, an alkenyl group having 2 to 12 carbon atoms, an alkenyloxy group having 2 to 8 carbon atoms, or a fluorine-substituted product of the above groups;
[0010] Ring A, Ring B, and Ring C each independently represent 1,4-phenylene, 1,4-cyclohexylene, 1,4-cyclohexenylene, tetrahydropyranylene, 1,3-dioxanylene, or fluorine-substituted products thereof;
[0011] Z1, Z2, and Z3 each independently represent a single bond, a double bond, O, -CF2O-, -OCF2-, -CH2O-, -OCH2-, -CH2CH2-, -COO-, -OCO-, -CHFO-, -OCHF-, -OCHFO-, -CF2-, -CHF-, -CH2-, -CHFCH2-, -CH2CHF-, -CHFCHF-, -CF2CH2-, -CH2CF2-, -CF2CHF-, -CHFCF2-, -CF2CF2-, -CH=CH-, -CF=CH-, -CH=CF-, or -CF=CF-;
[0012] m, n, and k each independently represent 0, 1 or 2.
[0013] As an embodiment of the present invention, in the general formula (I), R1 and R2 each independently represent an alkyl or alkoxy group having 1 to 5 carbon atoms, a cycloalkyl group having 3 to 5 carbon atoms, an alkenyl group having 2 to 6 carbon atoms, an alkenyloxy group having 2 to 8 carbon atoms, or a fluorine-substituted product of the above groups.
[0014] As a preferred embodiment of the present invention, in the general formula (I), R1 and R2 each independently represent an alkyl or alkoxy group having 1 to 5 carbon atoms, a cycloalkyl group having 3 to 5 carbon atoms, an alkenyl or alkenyloxy group having 2 to 4 carbon atoms, or fluorine-substituted products of the above groups.
[0015] As a further preferred embodiment of the present invention, in the general formula (I), R1 and R2 each independently represent an alkyl group, an alkoxy group, a fluoroalkyl group, a fluoroalkoxy group having 1 to 5 carbon atoms, a cycloalkyl group having 3 to 5 carbon atoms, an alkenyl group, a fluoroalkenyl group having 2 to 4 carbon atoms.
[0016] Among them, the alkyl group with 1-5 carbon atoms can be methyl, ethyl, propyl, butyl, pentyl; the alkoxy group with 1-5 carbon atoms can be methoxy, ethoxy, propoxy, butoxy, pentyl; the fluoroalkyl group can be a mono- or poly-fluoro group of methyl, ethyl, propyl, butyl or pentyl; the fluoroalkoxy group can be a mono- or poly-fluoro group of methoxy, ethoxy, propoxy, butoxy or pentyl, such as trifluoromethoxy; the cycloalkyl group with 3-5 carbon atoms can be cyclopropyl, cyclobutyl, cyclopentyl; the alkenyl group with 2-4 carbon atoms can be vinyl, propenyl, butenyl; the fluoroalkenyl group can be a mono- or poly-fluoro group of vinyl, propenyl or butenyl.
[0017] As an embodiment of the present invention, in the general formula (I), ring A, ring B, and ring C each independently represent 1,4-phenylene, 1,4-cyclohexylene, 1,4-cyclohexenylene, tetrahydropyranylene, 1,3-dioxanylene, or 1,4-phenylene in which at least one H is substituted by a fluorine atom.
[0018] As a preferred embodiment of the present invention, in the general formula (I), ring A, ring B, and ring C each independently represent: or
[0019] As an embodiment of the present invention, in the general formula (I), Z1, Z2, and Z3 each independently represent a single bond, -CF2O-, -OCF2-, -CH2O-, -OCH2-, -CH2CH2-, -COO-, -OCO-, or -CF2CF2-.
[0020] As a preferred embodiment of the present invention, in the general formula (I), Z1, Z2, and Z3 each independently represent a single bond, -CF2O-, -CH2O-, -CH2CH2-, or -COO-.
[0021] As an embodiment of the present invention, in the general formula (I), m, n, and k each independently represent 0 or 1.
[0022] As a preferred embodiment of the present invention, in the general formula (I), m and n each independently represent 0 or 1, and k is 0.
[0023] As an embodiment of the present invention, the liquid crystal compound includes a structure shown in any one of general formulas I-1 to I-124:
[0024]
[0025]
[0026]
[0027]
[0028]
[0029]
[0030]
[0031]
[0032]
[0033] In the above-mentioned general formulae I-1 to I-124, the definitions of R1 and R2 are the same as those of R1 and R2 in the above-mentioned general formula (I).
[0034] As a specific embodiment of the present invention, the liquid crystal compound provided by the present invention includes a compound represented by any of the following structures:
[0035]
[0036]
[0037]
[0038]
[0039]
[0040]
[0041]
[0042]
[0043]
[0044]
[0045]
[0046]
[0047]
[0048]
[0049]
[0050]
[0051]
[0052] In a second aspect, the present invention provides a liquid crystal material composition, wherein the liquid crystal material composition comprises the liquid crystal compound containing the polyfluorophenanthrene structure described in the present invention.
[0053] As an embodiment of the present invention, the content of the liquid crystal compound provided by the present invention in the liquid crystal material composition is 1 to 60% by weight, preferably 1 to 40% by weight, and more preferably 5 to 30% by weight.
[0054] In a third aspect, the present invention provides an application of the liquid crystal compound or the liquid crystal material composition described in the present invention in the field of liquid phase display.
[0055] Furthermore, the present invention provides use of the liquid crystal compound or the liquid crystal material composition of the present invention in a liquid display device, preferably used as a liquid crystal material in a liquid display device.
[0056] Preferably, the liquid crystal display device includes but is not limited to TN, ADS, VA, PSVA, FFS, and IPS liquid crystal displays.
[0057] The present invention provides a novel liquid crystal compound having a polyfluorophenanthrene unit structure. The liquid crystal compound has extremely high negative dielectric anisotropy and low rotational viscosity, thereby effectively reducing the driving voltage and improving the response speed of the liquid crystal display device. At the same time, it has the characteristics of moderate optical anisotropy value, high charge retention rate, etc. DETAILED DESCRIPTION
[0058] The technical scheme of the present invention is described in detail below. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. The raw materials can be obtained from public commercial channels unless otherwise specified.
[0059] It should be noted that the present invention obtains various performance parameters of liquid crystal compounds by linear fitting in accordance with conventional detection methods in the art, wherein the specific meaning of each performance parameter is as follows: Δε represents dielectric anisotropy (25°C, 1000 Hz); γ1 represents rotational viscosity (mPa·s, 25°C); △n represents optical anisotropy (25°C); Cp is the clearing point (°C).
[0060] Example 1 Synthesis of Compound LC-1
[0061]
[0062] The synthetic route is as follows:
[0063]
[0064] The specific steps of synthesis are:
[0065] (1) Under nitrogen protection, a solution of 4-bromo-1-ethoxy-2-trifluoromethylbenzene (M-01) (26.8 g, 0.1 mol) in THF (300 mL) was cooled to below -78°C, and lithium diisopropylamide LDA (99.1 mL, 0.11 mol) was slowly added dropwise. After the addition was complete, the mixture was stirred for 1 hour. DMF (10.95 g, 0.15 mol) was slowly added dropwise. After the addition was complete, the reaction solution was returned to room temperature, quenched in 100 ml of 1N-hydrochloric acid aqueous solution, and then extracted 3 times with 60 ml of toluene. The organic phase was washed with saturated sodium bicarbonate aqueous solution, water, and saturated saline, dried over anhydrous magnesium sulfate, filtered, and the solvent was dried by spin drying. The mixture was purified by silica gel column chromatography to obtain 11.8 g of white solid compound M-02 with a yield of 40%.
[0066] (2) A mixture of compound M-02 (29.6 g, 0.1 mol), ethylene glycol EG (18.0 g, 0.29 mol) and p-toluenesulfonamide PTSA (0.25 g, 1 wt%) was dissolved in 250 ml of toluene solvent and heated under reflux for 3 hours. The reaction solution was washed with saturated sodium bicarbonate aqueous solution, water, and saturated saline, dried over anhydrous magnesium sulfate, filtered, and the solvent was dried to obtain 33.7 g of white solid compound M-03, with a yield of 99%.
[0067] (3) Under nitrogen protection, compound M-03 (34.0 g, 0.1 mol) was dissolved in 350 ml of THF, then cooled to below -78 °C and n-butyl lithium (n-BuLi) (63.7 ml, 0.105 mol) was slowly added dropwise. After the reaction solution was stirred at below -78 °C for 1 hour, trimethyl borate (15.6 g, 0.15 mol) was slowly added dropwise. After the addition, the reaction solution was returned to room temperature, quenched in 200 ml of 2N-hydrochloric acid aqueous solution, extracted 3 times with 100 ml of toluene, the organic phases were combined, washed with saturated sodium bicarbonate aqueous solution, water, and saturated brine, dried over anhydrous magnesium sulfate, filtered, the solvent was spin-dried, rinsed with heptane and air-dried to obtain 19.7 g of white solid compound M-04, with a yield of 75%.
[0068] (4) Under nitrogen protection, a solution of 4-bromo-2-trifluoromethyl-1-propylbenzene (26.6 g, 0.1 mol) and THF (300 ml) was cooled to below -78°C, and lithium diisopropylamide LDA (99.1 ml, 0.11 mol) was slowly added dropwise. The reaction solution was stirred and reacted at below -78°C for 1 hour, and DMF (10.95 g, 0.15 mol) was added dropwise. The reaction solution was returned to room temperature, quenched in 100 ml of 1N-hydrochloric acid aqueous solution, and then extracted three times with 60 ml of toluene. The organic phases were combined, washed with saturated sodium bicarbonate aqueous solution, water, and saturated brine, dried over anhydrous magnesium sulfate, filtered, the solvent was spin-dried, and silica gel column chromatography was performed to obtain 11.8 g of white solid compound M-05, with a yield of 40%.
[0069] (5) Under nitrogen protection, M-05 (29.4 g, 0.1 mol), M-04 (39.3 g, 0.15 mol), potassium carbonate (27.6 g, 0.2 mol), tetrakis(triphenylphosphine)palladium (1.15 g, 0.001 mol), tetrabutylammonium bromide TBAB (4.84 g, 0.015 mol), 150 ml of toluene, 150 ml of isopropanol, and 150 ml of water were added to a 1 L reaction bottle and heated under reflux for 5 hours. The reaction solution was extracted 3 times with 60 ml of toluene. The organic phases were combined, washed with saturated sodium carbonate aqueous solution, water, and saturated brine, dried over anhydrous magnesium sulfate, filtered, the solvent was spin-dried, and purified by silica gel column chromatography to obtain 37.2 g of white solid compound M-06 with a yield of 86%.
[0070] (6) Under nitrogen protection, zinc powder (9.75 g, 0.15 mol) and zinc chloride (6.8 g, 0.752 mmol) were added to a DMF (450 ml) solution of compound M-06 (43.2 g, 0.1 mol), and the temperature was controlled at about 80°C and stirred for 8 hours. The reaction solution was quenched in 200 ml of 1N-hydrochloric acid aqueous solution, and then extracted with 60 ml of toluene three times. The organic phases were combined, washed with saturated sodium bicarbonate aqueous solution, water, and saturated brine, dried over anhydrous magnesium sulfate, filtered, the solvent was dried, and purified by silica gel column chromatography to obtain 26.9 g of white solid compound M-07, with a yield of 62%.
[0071] (7) Add 2-iodoacetylbenzoic acid IBX (112.0 g, 0.4 mol) to 400 ml of DMSO, stir at room temperature for 30 minutes, add compound M-07 (43.4 g, 0.1 mol), and continue stirring for 3 hours. Filter the reaction solution, add 200 ml of water to the filtrate, and then extract with 100 ml of ethyl acetate three times. Combine the organic phases, wash with saturated sodium bicarbonate aqueous solution, water, and saturated brine, dry with anhydrous magnesium sulfate, filter, spin dry the solvent, recrystallize from toluene, filter and dry to obtain 19.4 g of white solid compound M-08, with a yield of 45%.
[0072] (8) Under nitrogen protection, compound M-08 (43.0 g, 0.1 mol) and 400 ml of dichloromethane were added to the reaction flask, and stirring was started. The temperature was lowered to below -78°C, and diethylaminosulfur trifluoride DAST (96.6 g, 0.6 mol) was slowly added dropwise. After the addition was completed, the temperature was slowly raised to room temperature, quenched in 200 ml of water, and the liquids were separated. The organic phase was washed with saturated sodium bicarbonate aqueous solution, water, and saturated brine, dried over anhydrous magnesium sulfate, filtered, the solvent was spin-dried, and purified by silica gel column chromatography to obtain 34.1 g of white solid compound LC-1 with a yield of 72%.
[0073] Product LC-1: MS (m / z): 474 (M + ); Cp: 88.2℃; Δn is 0.124, Δε is -20.3, and γ1 is 141.4mPa·s.
[0074] 1 H NMR (400MHz, CDCl3): δ7.80-7.08(m,4H),4.11(q,2H),2.73(td,2H),1.65(qt,2H),1.43(d,3H),0.98(t,3H).
[0075] Example 2 Synthesis of Compound LC-8
[0076]
[0077] The synthetic route is as follows:
[0078]
[0079] The specific steps of synthesis are:
[0080] (1) Under nitrogen protection, add (35.0 g, 0.1 mol) 4-bromo-2-trifluoromethyl-1-iodobenzene and 300 ml THF to the reaction flask, start stirring, cool to below -78°C, and slowly drop n-BuLi (65.2 ml, 0.105 mol). Stir the reaction solution at below -78°C for 1 hour, and then slowly drop propyl cyclohexyl ketone (14.7 g, 0.105 mol). After the dropwise addition is complete, the reaction solution is returned to room temperature, quenched in 200 ml 1N-hydrochloric acid aqueous solution, and then extracted with 100 ml toluene for 3 times. Combine the organic phases, wash with saturated sodium bicarbonate aqueous solution, water, and saturated brine, dry over anhydrous magnesium sulfate, filter, spin dry the solvent, and purify by silica gel column chromatography to obtain 31.3 g of white solid LC-8-01, with a yield of 86%.
[0081] (2) Compound LC-8-01 (36.5 g, 0.1 mol), p-toluenesulfonamide PTSA (1.71 g, 0.01 mol), and 300 ml of toluene were added to the reaction flask and heated under reflux for 3 hours. The reaction solution was washed with saturated sodium bicarbonate aqueous solution, water, and saturated brine, dried over anhydrous magnesium sulfate, filtered, and the solvent was dried to obtain 34.3 g of white solid LC-8-02, with a yield of 99%.
[0082] (3) LC-8-02 (34.6 g, 0.1 mol), 3.5 g palladium carbon (50% water content), 100 mL toluene, and 100 mL ethanol were added to the hydrogenation kettle, stirred, and hydrogen was passed for 8 hours. The reaction mixture was monitored until no raw material was left. The palladium carbon was filtered, the solvent was evaporated, and the mixture was recrystallized from a mixed solvent of toluene and ethanol. The mixture was filtered and dried to obtain 17.4 g of white solid LC-8-03 with a yield of 50%.
[0083] (4) Under nitrogen protection, a solution of compound LC-8-03 (34.8 g, 0.1 mol) in THF (150 mL) was cooled to below -78°C, and lithium diisopropylamide LDA (99.1 mL, 0.11 mol) was slowly added dropwise. After the addition was completed, the mixture was stirred and reacted for 1 hour at below -78°C. DMF (10.95 g, 0.15 mol) was slowly added dropwise. After the addition was completed, the reaction solution was returned to room temperature, quenched in 100 ml of 1N-hydrochloric acid aqueous solution, and then extracted 3 times with 60 ml of toluene. The organic phase was washed with saturated sodium bicarbonate aqueous solution, water, and saturated brine, dried over anhydrous magnesium sulfate, filtered, and the solvent was dried by spin drying. The mixture was purified by silica gel column chromatography to obtain 15.5 g of white solid compound LC-8-04, with a yield of 41%.
[0084] The prepared LC-8-04 and the intermediate M-04 were reacted in sequence according to steps (5) to (8) in Example 1 to prepare 38.8 g of a white solid compound LC-8.
[0085] Product LC-8: MS (m / z): 556 (M + ); Cp: 99.7℃; Δn is 0.175, Δε is -22.1, and γ1 is 155.0mPa·s.
[0086] 1 H NMR (400MHz, CDCl3): δ7.80-7.08(m,4H),4.11(q,2H),3.08–2.99(m,1H),1.84–1.67(m,4H),1.60–1.18(m,12H),0.90(t,3H).
[0087] Example 3 Synthesis of Compound LC-13
[0088]
[0089] The synthetic route is as follows:
[0090]
[0091] The specific steps of synthesis are:
[0092] (1) Under nitrogen protection, 2-chloro-6-trifluoromethylbenzaldehyde (20.8 g, 0.1 mol), M-04 (28.8 g, 0.11 mol), potassium carbonate (27.6 g, 0.2 mol), Pd-132 (0.1 g), tetrabutylammonium bromide TBAB (6.45 g, 0.02 mol), 150 ml of toluene, 150 ml of isopropanol, and 150 ml of water were added to a 1 L reaction bottle and heated under reflux for 5 hours. The reaction solution was extracted three times with 100 ml of toluene. The organic phases were combined, washed with saturated sodium carbonate aqueous solution, water, and saturated brine, dried over anhydrous magnesium sulfate, filtered, the solvent was spin-dried, and purified by silica gel column chromatography to obtain 32.8 g of white solid compound LC-13-01, with a yield of 84%.
[0093] (2) Under nitrogen protection, a DMF (150 ml) solution of compound LC-13-01 (39.0 g, 0.1 mol), 3-ethyl-5-(2-hydroxyethyl)-4-methylthiazol-3-ium bromide (50.5 g, 0.2 mol) and triethylamine (30.3 g, 0.3 mol) was stirred at 60°C for 6 hours. The reaction solution was quenched in 150 ml of water and then extracted three times with 50 ml of dichloromethane. The organic phases were combined, washed with 1N-hydrochloric acid aqueous solution, water, and saturated brine, dried over anhydrous magnesium sulfate, filtered, and the solvent was dried to obtain 27.5 g of white solid compound LC-13-02, with a yield of 71%.
[0094] (3) Under nitrogen protection, compound LC-13-02 (38.8 g, 0.1 mol) and 400 ml of dichloromethane were added to the reaction flask, and stirring was started. The temperature was lowered to below -78°C, and diethylaminosulfur trifluoride DAST (72.5 g, 0.6 mol) was slowly added dropwise. After the addition was completed, the temperature was slowly raised to room temperature, quenched in 100 ml of water, and the liquids were separated. The organic phase was washed with saturated sodium bicarbonate aqueous solution, water, and saturated brine, dried over anhydrous magnesium sulfate, filtered, the solvent was spin-dried, and purified by silica gel column chromatography to obtain 38.9 g of white solid compound LC-13-03, with a yield of 90%.
[0095] (4) Under nitrogen protection, compound LC-13-03 (43.2 g, 0.1 mol) was dissolved in 350 ml THF, cooled to below -78°C, and n-butyl lithium (n-BuLi) (72.8 ml, 0.12 mol) was slowly added dropwise. After the reaction solution was stirred at below -78°C for 1 hour, a 100 ml THF solution of iodine (30.5 g, 0.12 mol) was added dropwise. After the addition was complete, the reaction solution was returned to room temperature, quenched in a saturated aqueous solution of ammonium chloride, extracted three times with 150 ml of toluene, and the organic phases were combined, washed with a saturated aqueous sodium bicarbonate solution, water, and saturated brine, dried over anhydrous magnesium sulfate, filtered, and the solvent was dried by spin drying, and purified by silica gel column chromatography to obtain 42.4 g of white solid compound LC-13-04, with a yield of 76%.
[0096] (5) Under nitrogen protection, LC-13-04 (55.8 g, 0.1 mol), 2-(4-propylphenyl)-1,3,2-dioxaborolane (38.0 g, 0.2 mol), potassium carbonate (27.6 g, 0.2 mol), tetrakis(triphenylphosphine)palladium (1.15 g, 0.001 mol), tetrabutylammonium bromide TBAB (4.84 g, 0.015 mol), 150 ml of toluene, 150 ml of ethanol, and 150 ml of water were added to the reaction flask and heated under reflux for 5 hours. The reaction solution was extracted three times with 60 ml of toluene. The organic phases were combined, washed with saturated sodium carbonate aqueous solution, water, and saturated brine, dried over anhydrous magnesium sulfate, filtered, the solvent was dried, and purified by silica gel column chromatography to obtain 47.9 g of white solid compound LC-13 with a yield of 87%.
[0097] Product LC-13: MS (m / z): 550 (M + ); Cp: 107.3℃; Δn is 0.258, Δε is -19.8, and γ1 is 156.2mPa·s.
[0098] 1 H NMR (400MHz, CDCl3): δ7.80-7.08(m,8H),4.11(q,2H),2.61(tt,2H),1.66(qt,2H),1.43(d,3H),0.96(t,3H).
[0099] Example 4 Synthesis of Compound LC-30
[0100]
[0101] The synthetic route is as follows:
[0102]
[0103] The specific steps of the synthesis are as follows: under nitrogen protection, LC-13-04 (55.8 g, 0.1 mol), (2,3-difluoro-4-(trifluoromethoxy)phenyl)boric acid (48.4 g, 0.2 mol), potassium carbonate (27.6 g, 0.2 mol), tetrakis(triphenylphosphine)palladium (1.15 g, 0.001 mol), tetrabutylammonium bromide TBAB (4.84 g, 0.015 mol), 150 ml of toluene, 150 ml of isopropanol, and 150 ml of water are added to the reaction bottle, and heated to reflux for 5 hours. The reaction solution is extracted 3 times with 60 ml of toluene. The organic phases are combined, washed with saturated sodium carbonate aqueous solution, water, and saturated brine, dried over anhydrous magnesium sulfate, filtered, the solvent is spin-dried, and purified by silica gel column chromatography to obtain 53.4 g of white solid compound LC-30 with a yield of 85%.
[0104] Product LC-30: MS (m / z): 628 (M + ); Cp: 143.4℃; Δn: 0.266, Δε: -23.3, γ1: 156.7mPa·s.
[0105] 1 H NMR (400MHz, CDCl3): δ7.80-7.08(m,6H),4.11(q,2H),1.43(d,3H).
[0106] Example 5 Synthesis of Compound LC-46
[0107]
[0108] The synthetic route is as follows:
[0109]
[0110] Referring to the synthesis operation of Example 1 and Example 2, propyl cyclohexyl ketone was replaced by ethyl cyclohexyl ketone. Instead of M-04, the target compound LC-46 was prepared.
[0111] Product LC-46: MS (m / z): 568 (M + ); Cp: 92.5℃; Δn is 0.201, Δε is -21.1, and γ1 is 142.3mPa·s.
[0112] 1H NMR (400MHz, CDCl3): δ7.81 -7.05(m,4H),5.89(tt,1H),4.01(t,2H),2.77-2.67(m,1H),2.67-2.58(m,1H),2.06 -1.91(m,2H),1.83 -1.54(m,5H),1.48(dt,2H),1.43-1.32(m,2H),0.98(t,3H),0.91(td,3H).
[0113] Example 6 Synthesis of Compound LC-79
[0114]
[0115] The specific steps of synthesis are:
[0116] (1) Under nitrogen protection, a suspension of triphenyl((4-propylcyclohexyl)methyl)phosphine iodide (58.1 g, 0.1 mol) in THF (500 ml) was cooled to below -30°C, and potassium tert-butoxide (12.3 g, 0.11 mol) was added. After the reaction solution was stirred at below -30°C for 1 hour, a solution of 4-bromo-2-trifluoromethylbenzaldehyde (25.2 g, 0.1 mol) in THF (100 ml) was added dropwise. After the reaction solution was restored to room temperature, it was quenched in 500 ml of water, and then extracted with 200 ml of toluene for 3 times. The organic phases were combined, washed with saturated brine, dried over anhydrous magnesium sulfate, filtered, the solvent was dried, and purified by silica gel column chromatography to obtain 35.5 g of white compound LC-79-01, with a yield of 95%.
[0117] (2) LC-79-01 (37.4 g, 0.1 mol), 3.7 g of palladium carbon (50% water content), 400 mL of toluene, and 200 mL of ethanol were added to the hydrogenation kettle, and the mixture was stirred and passed with hydrogen for 18 hours. The mixture was monitored until no raw material was left. The palladium carbon was filtered, the solvent was evaporated, and the mixture was subjected to silica gel column chromatography and recrystallized from a mixed solvent of heptane and ethanol. The mixture was filtered and dried to obtain 28.2 g of white solid LC-79-02 with a yield of 75%.
[0118] (3) Under nitrogen protection, a solution of LC-79-02 (37.6 g, 0.1 mol) in THF (300 ml) was cooled to below -78°C, and lithium diisopropylamide LDA (108.1 ml, 0.12 mol) was slowly added dropwise. The reaction solution was stirred at below -78°C for 1 hour, and DMF (10.95 g, 0.15 mol) was added dropwise. The reaction solution was returned to room temperature, quenched in 400 ml of 1N-hydrochloric acid aqueous solution, and then extracted three times with 200 ml of toluene. The organic phases were combined, washed with saturated sodium bicarbonate aqueous solution, water, and saturated brine, dried over anhydrous magnesium sulfate, filtered, the solvent was spin-dried, and silica gel column chromatography was performed to obtain 24.2 g of white solid compound LC-79-03, with a yield of 60%.
[0119] The prepared LC-79-03 and the intermediate M-04 were reacted in sequence according to steps (5) to (8) in Example 1 to prepare 40.9 g of white solid compound LC-79.
[0120] Product LC-79: MS (m / z): 584 (M + ); Cp: 97.4℃; Δn is 0.172, Δε is -18.4, γ1 is 158.4mPa·s.
[0121] 1 H NMR (400MHz, CDCl3): δ7.80 -7.08(m,4H),4.11(q,2H),2.77(td,1.0Hz,2H),1.76-1.60(m,2H),1.60-1.49(m,2H),1.47-1.20(m,16H),0.90(t,3H).
[0122] Example 7 Synthesis of Compound LC-105
[0123]
[0124] The synthetic route is as follows:
[0125]
[0126] The specific synthesis steps are:
[0127] (1) Under nitrogen protection, 4-bromo-2-trifluoromethyl-1-phenol (24.0 g, 0.1 mol), 1-(bromomethyl)-4-trifluoromethoxycyclohexane (26.0 g, 0.1 mol), potassium carbonate (27.6 g, 0.2 mol), and 250 ml of DMF were added to the reaction flask, and the temperature was raised to about 80°C for reaction for 5 hours. The reaction solution was quenched in 200 ml of water, and then extracted three times with 60 ml of toluene. The organic phases were combined, washed with 2N sodium hydroxide aqueous solution, water, and saturated brine, dried over anhydrous magnesium sulfate, filtered, the solvent was spin-dried, and purified by silica gel column chromatography to obtain 25.2 g of white solid compound LC-105-01, with a yield of 60%.
[0128] (2) Under nitrogen protection, a solution of LC-105-01 (42.0 g, 0.1 mol) in THF (300 ml) was cooled to below -78°C, and lithium diisopropylamide LDA (91.1 ml, 0.11 mol) was added dropwise. The reaction solution was stirred and reacted at below -78°C for 1 hour, and DMF (10.95 g, 0.15 mol) was slowly added dropwise. The reaction solution was returned to room temperature, quenched in 400 ml of 1N-hydrochloric acid aqueous solution, and then extracted three times with 200 ml of toluene. The organic phases were combined, washed with saturated sodium bicarbonate aqueous solution, water, and saturated brine, dried over anhydrous magnesium sulfate, filtered, the solvent was spin-dried, and silica gel column chromatography was performed to obtain 24.6 g of white solid compound LC-105-02, with a yield of 55%.
[0129] The prepared LC-105-02 and the intermediate M-04 were reacted in sequence according to steps (5) to (8) in Example 1 to prepare 35.1 g of a white solid compound LC-105.
[0130] Product LC-105: MS (m / z): 628 (M + ); Cp: 114.0℃; Δn is 0.177, Δε is -28.4, and γ1 is 175.3mPa·s.
[0131] 1 H NMR (400MHz, CDCl3): δ7.78-7.06(m,4H),4.11(q,2H),4.04-3.97(m,3H),2.02- 1.95(m,2H),1.98-1.92(m,1H),1.78-1.61(m,4H),1.53(dddd,2H),1.43(t,3H).
[0132] Example 8 Synthesis of Compound LC-164
[0133]
[0134] The synthetic route is as follows:
[0135]
[0136] The specific synthesis steps are:
[0137] (1) Under nitrogen protection, compound LC-13-03 (43.2 g, 0.1 mol) was dissolved in 400 ml THF, cooled to below -78°C, and n-butyl lithium (72.8 ml, 0.12 mol) was slowly added dropwise. After the reaction solution was stirred at below -78°C for 1 hour, trimethyl borate (12.5 g, 0.12 mol) was slowly added dropwise. After the addition was complete, the reaction solution was returned to room temperature, acetic acid (9.0 g, 0.15 mol) and hydrogen peroxide (6.8 g, 0.2 mol) were added, and the reaction was stirred for 3 hours. The reaction solution was quenched in a saturated aqueous ammonium chloride solution, and then extracted with 200 ml of toluene for 3 times. The organic phases were combined, washed with an aqueous sodium thiosulfate solution, a saturated aqueous sodium bicarbonate solution, water, and a saturated saline solution, dried over anhydrous magnesium sulfate, filtered, the solvent was dried, and purified by silica gel column chromatography to obtain 38.5 g of white solid compound LC-164-01, with a yield of 86%.
[0138] (2) Under nitrogen protection, compound LC-164-01 (44.8 g, 0.1 mol), potassium carbonate (27.6 g, 0.2 mol), and DMF 400 ml were added to the reaction flask, and the temperature was raised to 110°C for reaction for 1 hour. 1-Bromo-1-(bromodifluoromethyl)-4-propylcyclohexane (66.4 g, 0.2 mol) was added dropwise, and the reaction was continued with stirring for 3 hours. The reaction solution was quenched in water, and then extracted with 200 ml of toluene for 3 times. The organic phases were combined, washed with water and saturated brine, dried over anhydrous magnesium sulfate, filtered, the solvent was dried, and purified by silica gel column chromatography to obtain 49.6 g of white solid compound LC-164-02, with a yield of 80%.
[0139] (3) LC-164-02 (62.0 g, 0.1 mol), 6.2 g of palladium carbon (50% water content), 600 mL of toluene, and 300 mL of ethanol were added to the hydrogenation kettle. The mixture was stirred and hydrogen was passed for 24 hours. The mixture was monitored until no raw material was left. The palladium carbon was filtered, the solvent was evaporated, and the mixture was purified by silica gel column chromatography to obtain 43.5 g of white solid LC-164 with a yield of 70%.
[0140] Product LC-164: MS (m / z): 622 (M + ); Cp: 96.8℃; Δn is 0.156, Δε is -17.7, and γ1 is 142.2mPa·s.
[0141] 1H NMR (400MHz, CDCl3): δ7.78-7.08(m,4H),4.11(q,2H),2.52-2.36(m,1H),
[0142] 1.84-1.20(m,16H),0.90(t,3H).
[0143] Effect experiment example
[0144] The performance parameters of the liquid crystal compounds prepared in the above Examples 1 to 8 and the liquid crystal compounds of the comparative examples listed in Table 1 below were compared. The results are shown in Table 1.
[0145] Table 1 Performance test results of liquid crystal compounds
[0146]
[0147]
[0148] It can be clearly seen from the test results in Table 1 that the liquid crystal compounds provided by the present invention have higher negative dielectric anisotropy, moderate rotational viscosity γ1, and good low-temperature miscibility compared with compounds with similar chemical structures, which are exactly what is needed to improve liquid crystal materials. Therefore, the dielectric anisotropy △ε of the liquid crystal composition can be effectively improved, the driving voltage can be reduced, and a liquid crystal composition with a faster response speed can be obtained.
[0149] Mixed Crystal Example
[0150] The liquid crystal compound provided by the present invention and other liquid crystal monomers were prepared into a mixed crystal composition, and the performance was tested. The composition, ratio and test results of the mixed crystal composition are shown in Table 2 below. The ratio of the components is weight percentage.
[0151] Table 2 Composition and test results of mixed crystal examples and mixed crystal comparative examples
[0152]
[0153]
[0154] After the compounds described in the present application were specifically applied to liquid crystal compositions of conventional systems, it was found that they can improve the dielectric anisotropy △ε of the liquid crystal compositions while maintaining a relatively low rotational viscosity γ1 and an appropriate refractive index anisotropy △n. The resulting liquid crystal compositions have significant fast response characteristics and low voltage driving characteristics.
[0155] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A liquid crystal compound containing a polyfluorophenanthrene structure, characterized in that: Including the structure shown in general formula (I): in: R1 and R2 each independently represent an alkyl group or alkoxy group having 1 to 12 carbon atoms, a cycloalkyl group having 3 to 8 carbon atoms, an alkenyl group having 2 to 12 carbon atoms, an alkenyloxy group having 2 to 8 carbon atoms, or a fluorine-substituted product of the above groups; Ring A, Ring B, and Ring C each independently represent 1,4-phenylene, 1,4-cyclohexylene, 1,4-cyclohexenylene, tetrahydropyranylene, 1,3-dioxanylene, or fluorine-substituted products thereof; Z1, Z2, and Z3 each independently represent a single bond, a double bond, O, -CF2O-, -OCF2-, -CH2O-, -OCH2-, -CH2CH2-, -COO-, -OCO-, -CHFO-, -OCHF-, -OCHFO-, -CF2-, -CHF-, -CH2-, -CHFCH2-, -CH2CHF-, -CHFCHF-, -CF2CH2-, -CH2CF2-, -CF2CHF-, -CHFCF2-, -CF2CF2-, -CH=CH-, -CF=CH-, -CH=CF-, or -CF=CF-; m, n, and k each independently represent 0, 1 or 2.
2. The liquid crystal compound according to claim 1, characterized in that The R1 and R2 each independently represent an alkyl or alkoxy group having 1 to 5 carbon atoms, a cycloalkyl group having 3 to 5 carbon atoms, an alkenyl group having 2 to 6 carbon atoms, an alkenyloxy group having 2 to 8 carbon atoms, or fluorine-substituted products of the above groups.
3. The liquid crystal compound according to claim 1, characterized in that The R1 and R2 each independently represent an alkyl or alkoxy group having 1 to 5 carbon atoms, a cycloalkyl group having 3 to 5 carbon atoms, an alkenyl or alkenyloxy group having 2 to 4 carbon atoms, or fluorine-substituted products of the above groups.
4. The liquid crystal compound according to claim 1, characterized in that The R1 and R2 each independently represent an alkyl group, an alkoxy group, a fluoroalkyl group, a fluoroalkoxy group having 1 to 5 carbon atoms, a cycloalkyl group having 3 to 5 carbon atoms, an alkenyl group, a fluoroalkenyl group having 2 to 4 carbon atoms.
5. The liquid crystal compound according to claim 1, characterized in that The ring A, ring B and ring C each independently represent 1,4-phenylene, 1,4-cyclohexylene, 1,4-cyclohexenylene, tetrahydropyranylene, 1,3-dioxanylene or 1,4-phenylene in which at least one H is substituted by a fluorine atom.
6. The liquid crystal compound according to claim 1, characterized in that The ring A, ring B and ring C are each independently represented by:
7. The liquid crystal compound according to claim 6, characterized in that: The Z1, Z2, and Z3 each independently represent a single bond, -CF2O-, -OCF2-, -CH2O-, -OCH2-, -CH2CH2-, -COO-, -OCO-, or -CF2CF2-.
8. The liquid crystal compound according to claim 6, characterized in that: Z1, Z2, and Z3 each independently represent a single bond, -CF2O-, -CH2O-, -CH2CH2-, or -COO-.
9. The liquid crystal compound according to claim 1, characterized in that: The m, n, and k each independently represent 0 or 1.
10. The liquid crystal compound according to claim 1, characterized in that: The m and n each independently represent 0 or 1, and k is 0.
11. The liquid crystal compound according to any one of claims 1 to 10, characterized in that: The liquid crystal compound includes a structure shown in any one of general formulas I-1 to I-124:
12. The liquid crystal compound according to claim 11, characterized in that: The liquid crystal compound includes a compound represented by any of the following structures:
13. A liquid crystal material composition, characterized in that: The liquid crystal material composition comprises the liquid crystal compound according to any one of claims 1 to 12.
14. The liquid crystal material composition according to claim 13, characterized in that: The content of the liquid crystal compound in the composition is 1 to 60% by weight.
15. The liquid crystal material composition according to claim 13, characterized in that: The content of the liquid crystal compound in the composition is 1 to 40% by weight.
16. The liquid crystal material composition according to claim 13, characterized in that: The content of the liquid crystal compound in the composition is 5 to 30% by weight.
17. Use of the liquid crystal compound according to any one of claims 1 to 12 or the liquid crystal material composition according to any one of claims 13 to 16 in the field of liquid crystal display.
18. Use of the liquid crystal compound according to any one of claims 1 to 12 or the liquid crystal material composition according to any one of claims 13 to 16 in a liquid crystal display device.
19. The use according to claim 18, characterized in that The liquid crystal display device includes TN, ADS, VA, PSVA, FFS, and IPS liquid crystal displays.
Citation Information
Patent Citations
Compound containing dihydrophenanthrene, liquid crystal composition and liquid crystal display
CN103261132A
4,5-di-substituted phenanthrene and hydrophenanthrene liquid crystal compound and preparation method thereof
CN104557481A